2021
DOI: 10.1111/papr.13078
|View full text |Cite
|
Sign up to set email alerts
|

Clinical comparison of unilateral biportal endoscopic discectomy with percutaneous endoscopic lumbar discectomy for single l4/5‐level lumbar disk herniation

Abstract: Objective The purpose of this research was to investigate the outcomes between unilateral biportal endoscopic discectomy (UBE) and percutaneous endoscopic lumbar discectomy (PELD) for the single L4/5‐level lumbar disk herniation (sLDH). Methods From January 2018 to January 2021, a total of 40 patients with sLDH were retrospectively analyzed in this study. All the patients had received spinal surgeries in Affiliated Hospital of Nantong University and Affiliated Nantong Hospital 3 of Nantong University. Among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 31 publications
4
19
0
1
Order By: Relevance
“…ODI scores reflect functional recovery of patients after surgery. Both UBE and PELD were effective in promoting functional recovery in patients, but there was no significant difference between them, which is consistent with the findings of the study by Hao et al [ 17 ]. Our study found no difference between UBE and PELD in terms of complications, and UBE has the same safety profile as PELD.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…ODI scores reflect functional recovery of patients after surgery. Both UBE and PELD were effective in promoting functional recovery in patients, but there was no significant difference between them, which is consistent with the findings of the study by Hao et al [ 17 ]. Our study found no difference between UBE and PELD in terms of complications, and UBE has the same safety profile as PELD.…”
Section: Discussionsupporting
confidence: 91%
“…Two studies [ 17 , 18 ] reported complications between UBE and PELD (94 patients, 44 in the UBE group and 50 in the PELD group). Meta-analysis showed no statistically significant difference in complications between the two groups (WMD = 2.53, 95% CI (0.40, 16.11), P = 0.33, heterogeneity: χ 2 = 0.10, df = 1 ( P = 0.76), I 2 = 0%).…”
Section: Resultsmentioning
confidence: 99%
“…The study selection flow chart is shown in Figure 1. The 16 eligible articles (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) included 19 comparison groups, with a combined 653 patients who underwent UBE, 612 who underwent MED, 153 who underwent PELD, and 70 who underwent PLIF. Of the 16 included articles, 2 were RCTs, 5 were cohort studies, and 9 were case-control studies.…”
Section: Study Selectionmentioning
confidence: 99%
“…It is mainly divided into the TF and the IL different surgical approaches and is widely used in clinical practice. Even when compared with other types of minimally invasive surgery, such as MIS-TLIF and unilateral biportal endoscopic discectomy, PELD performed obviously less intraoperative blood loss, shorter operative time, lighter low back, and leg pain postoperative ( 7 , 8 ). Although it has minimally invasive features, PELD requires the destruction of back soft tissue and lumbar disc structure, which inevitably leads to postoperative pain and recurrence in patients, and recurrence rates of LDH have been reported in the literature ranging from 5 to 15 percent ( 9 ).…”
Section: Discussionmentioning
confidence: 94%